Helio-aero-gravity electric power production at low cost - Lodhi, M.A.K.; Sulaiman, M.Yusof (Elsevier, 1992)
The power production from the helio-aero-gravity concept can be demonstrated by selecting a flat patch of land in an isolated desert where solar radiation is abundant. The land may be sprayed with black paint and canopied with some transparent material. A chimney containing an air turbine is to be installed at the center of the black patch. At the periphery of the patch, the canopy should be kept above the ground leaving sufficient space for cold air to enter the region under the canopy. The black patch is heated by direct sun's radiation entering through the transparent cover. The cold air gets heated as it moves over the heated land surface under the canopy. Due to the pressure difference, the hot air will rise into the chimney and drive the turbine. The power thus generated could be about 50 MW per kilometer square of land at a low cost of per energy unit. A systematic theoretical study is carried out to investigate the scientific and technical merits of this system for large scale power production, in particular to investigate heat transfer processes in the system in a quantitative manner.